Long-term safety and efficacy of sarilumab plus methotrexate on disease activity, physical function and radiographic progression: 5 years of sarilumab plus methotrexate treatment. Issue 2 (1st August 2019) - Genovese, Mark C; van der Heijde, Désirée; Lin, Yong; St John, Gregory; Wang, Sheldon; van Hoogstraten, Hubert; Gómez-Reino, Juan José; Kivitz, Alan; Maldonado-Cocco, José Antonio; Seriolo, Bruno; Stanislav, Marina; Burmester, Gerd R
Abstract : Objective: In MOBILITY (NCT01061736 ), sarilumab significantly reduced disease activity, improved physical function and inhibited radiographic progression at week 52 versus placebo in patients with rheumatoid arthritis (RA) and an inadequate response to methotrexate. We report 5-year safety, efficacy and radiographic outcomes of sarilumab from NCT01061736 and the open-label extension (EXTEND; NCT01146652 ), in which patients received sarilumab 200 mg every 2 weeks (q2w) + methotrexate. Methods: Patients (n=1197) with moderately to severely active RA were initially randomised to placebo, sarilumab 150 mg or sarilumab 200 mg subcutaneously q2w plus weekly methotrexate for 52 weeks. Completers were eligible to enrol in the open-label extension and receive sarilumab 200 mg q2w + methotrexate. Results: Overall, 901 patients entered the open-label extension. The safety profile remained stable over 5-year follow-up and consistent with interleukin-6 receptor blockade. Absolute neutrophil count <1000 cells/mm 3 was observed but not associated with increased infection rate. Initial treatment with sarilumab 200 mg + methotrexate was associated with reduced radiographic progression over 5 years versus sarilumab 150 mg + methotrexate or placebo + methotrexate (mean±SE change from baseline in van der Heijde-modified Total Sharp Score: 1.46±0.27, 2.35±0.28 and 3.68±0.27, respectively (p<0.001 for each sarilumab dose versus placebo)). Clinical efficacy was sustained through 5 years according to Disease Activity Score (28-joint count) using C reactive protein, Clinical Disease Activity Index (CDAI) and Health Assessment Questionnaire-Disability Index. The number of patients achieving CDAI ≤2.8 at 5 years was similar among initial randomisation groups (placebo, 76/398 (19%); sarilumab 150 mg, 68/400 (17%); sarilumab 200 mg, 84/399 (21%)). Conclusion: Clinical efficacy, including inhibition of radiographic progression, reduction in disease activity and improvement in physical function, was sustained with sarilumab + methotrexate over 5 years. Safety appeared stable over the 5-year period.